Metal nitride-based composite coating and preparation method thereof

By preparing metal nitride-based composite coatings under high-power pulse magnetron sputtering technology, combined with the advantages of MoN and MoS2, the poor lubrication effect of MoS2-based thin film materials at high temperatures and high friction coefficient of MoN coatings in the prior art are solved. The problem of low friction lubrication effect is achieved under high contact stress, medium and high temperature and high vacuum environment.

CN119433447APending Publication Date: 2025-02-14LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411630637.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing MoS2-based film materials have poor lubrication effect in high temperature environments and have a high friction coefficient of MoN coating, which cannot meet the lubrication needs of space bearings under high contact stress, medium and high temperature and high vacuum environments.

Method used

The metal nitride-based composite coating is prepared by high-power pulse magnetron sputtering technology. MoN is used as the base phase, the high-entropy alloy Cr-Al-Ti-Nb-V is used as the reinforced phase, and MoS2 and Ag are used as the lubricating phase to form a dense Micro-morphology to improve the uniformity and density of the coating.

Benefits of technology

In a vacuum environment with high contact stress 1GPa and 400°C, the average friction coefficient of the MoN-based self-lubricating composite coating is reduced to 0.14, meeting the lubrication and protection needs of space bearings in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433447A_ABST
    Figure CN119433447A_ABST
Patent Text Reader

Abstract

The invention provides a metal nitride-based composite coating and a preparation method thereof, and relates to the technical field of solid lubricating coatings, the metal nitride-based composite coating is composed of MoN metal nitride as a basic phase, high-entropy alloy (Cr-Al-Ti-Nb-V) doped as a reinforcing phase of MoN, and MoS2 and Ag as a lubricating phase. The preparation method comprises the following steps: depositing the MoN-based composite coating of Cr-Al-Ti-Nb-V compounded MoS2 and Ag on the surface of the substrate by adopting a high-power pulse magnetron sputtering technology. The preparation method has the beneficial effects that the defects that the MoS2-based thin film material is poor in lubricating performance in a high-temperature environment and the MoN coating is high in friction coefficient are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a metal nitride-based composite coating and a preparation method thereof, and relates to the technical field of solid lubricating coatings. Background Art

[0002] Sputtered MoS2 thin film material has excellent lubrication performance in vacuum environment due to its layered structure and has been widely used as solid lubricant for space. Since MoS2 is a low-temperature lubricant with a heat resistance temperature below 350°C, at high temperatures, the crystallized MoS2 film is prone to severe oxidation and produces a large number of wear particles, leading to its rapid failure. It can be seen that the film faces serious oxidation and wear problems in vacuum and high temperature environments. At present, the film is mainly used for lubrication of mechanical moving parts under conditions where the temperature is below 200°C and the contact stress is several hundred MPa.

[0003] With the development of space high technology, some space bearing components need to operate multiple times under extremely harsh conditions of high temperature (above 350°C) and high contact stress (several GPa). Therefore, the existing MoS2-based thin film materials can no longer meet the actual lubrication needs of such components. MoN coating has the advantages of high temperature oxidation resistance, excellent wear resistance and high temperature mechanical properties, and is an excellent high temperature lubrication material, but its friction coefficient is high. Summary of the invention

[0004] The present invention provides a metal nitride-based composite coating and a preparation method thereof, which solves the technical problems in the prior art that the lubrication effect of MoS2-based thin film materials is poor in a high temperature environment and the friction coefficient of the MoN coating is high.

[0005] The present invention is achieved in that the metal nitride-based composite coating is composed of MoN as a basic phase, high entropy alloy doping as a reinforcement phase of MoN, and MoS2 and Ag as lubricating phases.

[0006] As a further preference, the high entropy alloy is Cr-Al-Ti-Nb-V.

[0007] As a further preference, the metal ratios of the high entropy alloy are: (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%)V.

[0008] As a further preference, the thickness of the metal nitride-based composite coating is 1300nm to 2000nm.

[0009] The invention discloses a method for preparing a metal nitride-based composite coating, which adopts a high-power pulsed magnetron sputtering technology to deposit a Mo transition layer and a MoN-based composite coating of Cr-Al-Ti-Nb-V compounded with MoS2 and Ag on the surface of a substrate.

[0010] As a further preference, the method for depositing the Mo transition layer includes: using high-power pulsed magnetron sputtering technology, using Mo as a target material, using an inert gas as a working gas, applying a high-power pulse power supply to the Mo target, and applying a bias voltage at the same time, wherein the inert gas flow rate is 60sccm, the substrate bias is -200 to -300V, the frequency is 80KHz, the pulse width is 6μs, the peak current is 260A, the average output power is 5KW, the frequency is 100Hz, the pulse width is 500μs, and the deposition time is 10 to 15min.

[0011] As a further preferred method, the method for depositing the MoN-based composite coating includes: using high-power pulsed magnetron sputtering technology, using Mo, (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%)V compounded with MoS2 and Ag as target materials, using inert gas as working gas, and inputting nitrogen at the same time, High-power pulse power supply and pulse bias were applied to the Mo target, high-entropy alloy composite MoS2 and Ag target at the same time, among which, the peak current of the Mo target was 260A, the average output power was 5KW, the frequency was 100Hz, the pulse width was 500μs, the inert gas flow rate was 60sccm, the N2 flow rate was 10sccm~20sccm, the bias was -150V, the frequency was 40KHz, the pulse width was 12μs, the peak current of the high-entropy alloy composite MoS2 target and the Ag target was 40A~80A, and the deposition time was 180min.

[0012] The beneficial effects of the present invention are as follows: the thickness of the coating prepared by the present invention is about 1300-2000nm, and the prepared coating presents a dense microscopic morphology. The present invention adopts high-power pulsed magnetron sputtering technology to improve the ionization rate of the sputtering material, generate a high plasma density, enhance the energy of the deposited atoms, and can significantly improve the uniformity and density of the coating during deposition, thereby realizing the controllable preparation of high-quality coatings. The present invention introduces MoN high-temperature lubricating material, which plays a high load-bearing role and strong resistance to plastic deformation and has a certain lubricity at high temperature. The mechanical properties and high-temperature lubricity of MoN are further improved by doping an appropriate amount of high-entropy alloy Cr-Al-Ti-Nb-V. MoS2 and Ag are used as lubricating phases, and tribochemical reactions will occur with MoN at medium and high temperatures to form a high-temperature lubricating phase, thereby achieving low friction. Through the regulation and optimization of the preparation process, a MoN-based self-lubricating composite coating with good lubrication performance and excellent mechanical properties is prepared. The average friction coefficient of the MoN-based self-lubricating composite coating is reduced to 0.14 in a vacuum environment with a high contact stress of 1GPa and 400°C. The coating provided by the present invention can meet the lubrication and protection requirements of space bearings in harsh working conditions such as high contact stress, medium and high temperature, and high vacuum when in service. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a cross-sectional SEM image of the coating prepared in Example 1;

[0014] Figure 2 is the friction coefficient curve of the coating prepared in Example 1 under a vacuum environment at 400°C;

[0015] Figure 3 is a cross-sectional SEM image of the coating prepared in Example 2;

[0016] Figure 4 is the friction coefficient curve of the coating prepared in Example 2 under a vacuum environment at 400°C;

[0017] Figure 5 is a cross-sectional SEM image of the coating prepared in Example 3;

[0018] Figure 6 This is the friction coefficient curve of the coating prepared in Example 3 under a vacuum environment at 400°C. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The metal nitride-based composite coating is composed of MoN as the base phase, high entropy alloy doping as the reinforcement phase of MoN, and MoS2 and Ag as the lubricating phase. It combines the advantages of MoN and MoS2, overcomes the disadvantages of both, improves the friction performance of MoN, and increases the application temperature of MoS2.

[0021] As a further preference, the high entropy alloy is (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%)V.

[0022] As a further preference, the thickness of the metal nitride-based composite coating is 1300nm to 2000nm.

[0023] The invention discloses a preparation method of a metal nitride-based composite coating, which adopts high-power pulsed magnetron sputtering technology to deposit a Mo transition layer and a MoN-based composite coating of Cr-Al-Ti-Nb-V compounded with MoS2 and Ag on the surface of a substrate, wherein MoN is used as a basic phase, Cr-Al-Ti-Nb-V is used as a reinforcing phase, and MoS2 and Ag are used as lubricating phases.

[0024] Furthermore, the substrate is a high temperature steel substrate, including but not limited to 8Cr4Mo4V steel and Inconel 718 alloy steel.

[0025] As a further preference, the method for depositing the Mo transition layer includes: using high-power pulsed magnetron sputtering technology, using Mo as a target material, using an inert gas as a working gas, applying a high-power pulse power supply to the Mo target, and applying a bias voltage at the same time, wherein the inert gas flow rate is 60sccm, the substrate bias is -200 to -300V, the frequency is 80KHz, the pulse width is 6μs, the peak current is 260A, the average output power is 5KW, the frequency is 100Hz, the pulse width is 500μs, and the deposition time is 10 to 15min.

[0026] Furthermore, the inert gas includes but is not limited to argon.

[0027] Furthermore, the Mo target is a pure Mo target.

[0028] As a further preference, the method for depositing the MoN-based composite coating includes: using high-power pulsed magnetron sputtering technology, using Mo and (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%)V compounded MoS2 and Ag as target materials, Cr-Al-Ti-Nb-V compounded MoS2 and Ag as one target material, using inert gas as working gas, and simultaneously inputting nitrogen, applying high-power pulse power to the Mo target, MoS2 target, Cr-Al-Ti-Nb-V target, and Ag target. At the same time, a pulse bias is applied, wherein the peak current of the Mo target is 260A, the average output power is 5KW, the frequency is 100Hz, the pulse width is 500μs, the inert gas flow rate is 60sccm, the N2 flow rate is 10sccm~20sccm, the bias voltage is -150V, the frequency is 40KHz, the pulse width is 12μs, the peak current of the (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%)V composite MoS2 and Ag target is 40A~80A, and the deposition time is 180min.

[0029] Furthermore, the inert gas includes but is not limited to argon.

[0030] As a further preference, before depositing the Mo transition layer and the MoN-based composite coating on the substrate, the substrate is cleaned and dried, and then ion-etched.

[0031] Furthermore, the substrate cleaning and drying method is specifically as follows: ultrasonic cleaning with anhydrous ethanol and petroleum ether for 30 minutes respectively, and then placing it in a drying chamber after drying.

[0032] Furthermore, the substrate ion etching method is specifically as follows: placing the substrate in a vacuum chamber for evacuation, heating the chamber temperature to 350°C, and the vacuum degree is less than 1×10 -3 Pa, start ion etching on the substrate surface, introduce Ar with a flow rate of 400sccm, apply a pulse bias on the steel block sample with a bias of -850V, a frequency of 40KHz, and a pulse width of 4μs, and use Ar plasma to pre-sputter clean the steel block sample for 30 minutes.

[0033] Example 1

[0034] A high-temperature self-lubricating metal nitride-based composite coating for space use and a preparation method thereof, wherein the coating is prepared by high-power pulsed magnetron sputtering technology, and the specific steps are as follows:

[0035] (1) Pretreatment

[0036] The 8Cr4Mo4V steel substrate was ultrasonically cleaned with anhydrous ethanol and petroleum ether for 30 min respectively, and then dried and placed in a drying chamber for later use;

[0037] (2) Pre-sputtering cleaning

[0038] The high temperature alloy steel substrate treated in step (1) is placed in a vacuum chamber for evacuation. The chamber temperature is heated to 350°C and the vacuum degree is less than 1×10 -3 Pa, ion etching was started on the surface of the high-temperature alloy steel substrate, Ar was introduced at a flow rate of 400 sccm, a pulse bias voltage of -850 V, a frequency of 40 KHz, and a pulse width of 4 μs was applied to the high-temperature alloy steel substrate, and the high-temperature alloy steel substrate was pre-sputtered and cleaned with Ar plasma for 30 minutes;

[0039] (3) Deposition of Mo transition layer

[0040] Adopt high-power pulse magnetron sputtering technology, adjust Ar flow rate to 60sccm, continuously adjust substrate bias to -200~-300V, frequency to 80KHz, pulse width to 6μs, apply high-power pulse power supply to pure Mo target, adjust peak current to 260A, average output power to 5KW, frequency to 100Hz, pulse width to 500μs, deposition time to 10~15min, deposit Mo transition layer;

[0041] (4) Deposition of MoN-based composite coating

[0042] High-power pulsed magnetron sputtering technology was adopted to keep the peak current and average output power of the Mo target unchanged, the frequency was 100 Hz, the pulse width was 500 μs, the Ar flow rate was unchanged, and N2 with a flow rate of 10 sccm was introduced. A pulse bias was applied to the steel block sample, with a bias of -150 V, a frequency of 40 kHz, a pulse width of 12 μs, a peak current of 40 A for the 0.17 at% Cr-0.08 at% Al-0.21 at% Ti-0.13 at% Nb-0.41 at% V composite MoS2 and Ag target, and a deposition time of 180 min to deposit a MoN-based composite coating.

[0043] See also Figure 1 , the coating thickness prepared in Example 1 is about 1500nm. The tribological performance of the composite coating of Example 1 was tested using a CSM vacuum friction tester. While the cavity was evacuated, the heating device was turned on. When the vacuum chamber temperature reached 400°C and the vacuum degree was lower than 0.001Pa, the friction test was started. The load applied during the friction process was 10N, the reciprocating frequency was 1Hz, and the friction coefficient protection value was set to 0.5. Figure 2The average friction coefficient of the coating in a vacuum environment at 400°C is about 0.38.

[0044] Example 2

[0045] A high-temperature self-lubricating metal nitride-based composite coating for space use and a preparation method thereof, wherein the coating is prepared by high-power pulsed magnetron sputtering technology, and the specific steps are as follows:

[0046] (1) Pretreatment

[0047] The 8Cr4Mo4V steel substrate was ultrasonically cleaned with anhydrous ethanol and petroleum ether for 30 min respectively, and then dried and placed in a drying chamber for later use;

[0048] (2) Pre-sputtering cleaning

[0049] The high temperature alloy steel substrate treated in step (1) is placed in a vacuum chamber for evacuation. The chamber temperature is heated to 350°C and the vacuum degree is less than 1×10 -3 Pa, ion etching was started on the surface of the high-temperature alloy steel substrate, Ar was introduced at a flow rate of 400 sccm, a pulse bias voltage of -850 V, a frequency of 40 KHz, and a pulse width of 4 μs was applied to the high-temperature alloy steel substrate, and the high-temperature alloy steel substrate was pre-sputtered and cleaned with Ar plasma for 30 minutes;

[0050] (3) Deposition of Mo transition layer

[0051] Adopt high-power pulse magnetron sputtering technology, adjust Ar flow rate to 60sccm, continuously adjust substrate bias to -200~-300V, frequency to 80KHz, pulse width to 6μs, apply high-power pulse power supply to pure Mo target, adjust peak current to 260A, average output power to 5KW, frequency to 100Hz, pulse width to 500μs, deposition time to 10~15min, deposit Mo transition layer;

[0052] (4) Deposition of MoN-based composite coating

[0053] High-power pulsed magnetron sputtering technology was used to keep the peak current and average output power of the Mo target unchanged, the frequency was 100 Hz, the pulse width was 500 μs, the Ar flow rate was unchanged, and 15 sccm of N2 was introduced. A pulse bias was applied to the steel block sample, with a bias of -150 V, a frequency of 40 kHz, and a pulse width of 12 μs. The peak current of the 0.41 at% Cr-0.21 at% Al-0.13 at% Ti-0.08 at% Nb-0.17 at% V composite MoS2 and Ag target was adjusted to 60 A, the deposition time was 180 min, and a MoN-based composite coating was deposited.

[0054] See also Figure 3, the coating thickness prepared in Example 2 is about 2000nm. Figure 4 The tribological properties of the composite coating of Example 1 were tested using a CSM vacuum friction tester. While the cavity was evacuated, the heating device was turned on. The friction test was started when the vacuum chamber temperature reached 400°C and the vacuum degree was lower than 0.001 Pa. The load applied during the friction process was 10N, the reciprocating frequency was 1Hz, and the average friction coefficient was about 0.14.

[0055] Example 3

[0056] A high-temperature self-lubricating metal nitride-based composite coating for space use and a preparation method thereof, wherein the coating is prepared by high-power pulsed magnetron sputtering technology, and the specific steps are as follows:

[0057] (1) Pretreatment

[0058] The 8Cr4Mo4V steel substrate was ultrasonically cleaned with anhydrous ethanol and petroleum ether for 30 min respectively, and then dried and placed in a drying chamber for later use;

[0059] (2) Pre-sputtering cleaning

[0060] The high temperature alloy steel substrate treated in step (1) is placed in a vacuum chamber for evacuation. The chamber temperature is heated to 350°C and the vacuum degree is less than 1×10 -3 Pa, ion etching was started on the surface of the high-temperature alloy steel substrate, Ar was introduced at a flow rate of 400 sccm, a pulse bias voltage of -850 V, a frequency of 40 KHz, and a pulse width of 4 μs was applied to the high-temperature alloy steel substrate, and the high-temperature alloy steel substrate was pre-sputtered and cleaned with Ar plasma for 30 minutes;

[0061] (3) Deposition of Mo transition layer

[0062] Adopt high-power pulse magnetron sputtering technology, adjust Ar flow rate to 60sccm, continuously adjust substrate bias to -200~-300V, frequency to 80KHz, pulse width to 6μs, apply high-power pulse power supply to pure Mo target, adjust peak current to 260A, average output power to 5KW, frequency to 100Hz, pulse width to 500μs, deposition time to 10~15min, deposit Mo transition layer;

[0063] (4) Deposition of MoN-based composite coating

[0064] High-power pulsed magnetron sputtering technology was used to keep the peak current and average output power of the Mo target unchanged, the frequency was 100 Hz, the pulse width was 500 μs, the Ar flow rate was unchanged, 20 sccm of N2 was introduced, a pulse bias was applied to the steel block sample, the bias was -150 V, the frequency was 40 kHz, the pulse width was 12 μs, the peak current of the 0.41 at% Cr-0.21 at% Al-0.13 at% Ti-0.08 at% Nb-0.17 at% V composite MoS2 and Ag target was adjusted to 80 A, the deposition time was 180 min, and a MoN-based composite coating was deposited.

[0065] See also Figure 5 , the coating thickness prepared in Example 3 is about 1300nm. Figure 6 The tribological properties of the composite coating of Example 1 were tested using a CSM vacuum friction tester. While the cavity was evacuated, the heating device was turned on. The friction test was started when the temperature of the vacuum chamber reached 400°C and the vacuum degree was lower than 0.001 Pa. The load applied during the friction process was 10N, the reciprocating frequency was 1Hz, and the average friction coefficient was about 0.18.

[0066] The beneficial effects of the present invention are as follows: the thickness of the coating prepared by the present invention is about 1300-2000nm, and the prepared coating presents a dense microscopic morphology. The present invention adopts high-power pulsed magnetron sputtering technology to improve the ionization rate of the sputtering material, generate a high plasma density, enhance the energy of the deposited atoms, and can significantly improve the uniformity and density of the coating during deposition, thereby realizing the controllable preparation of high-quality coatings. The present invention introduces MoN high-temperature lubricating material, which plays a high load-bearing role and strong resistance to plastic deformation and has a certain lubricity at high temperature. The mechanical properties and high-temperature lubricity of MoN are further improved by doping an appropriate amount of high-entropy alloy Cr-Al-Ti-Nb-V. MoS2 and Ag are used as lubricating phases, and tribochemical reactions will occur with MoN at medium and high temperatures to form a high-temperature lubricating phase, thereby achieving low friction. Through the regulation and optimization of the preparation process, a MoN-based self-lubricating composite coating with good lubrication performance and excellent mechanical properties is prepared. The average friction coefficient of the MoN-based self-lubricating composite coating is reduced to 0.14 in a vacuum environment with a high contact stress of 1GPa and 400°C. The coating provided by the present invention can meet the lubrication and protection requirements of space bearings in harsh working conditions such as high contact stress, medium and high temperature, and high vacuum when in service.

[0067] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A metal nitride-based composite coating, characterized in that: The metal nitride-based composite coating is composed of MoN as a basic phase, high entropy alloy doping as a reinforcement phase of MoN, and MoS2 and Ag as lubricating phases.

2. The metal nitride-based composite coating according to claim 1, characterized in that: The high entropy alloy is Cr-Al-Ti-Nb-V.

3. The metal nitride-based composite coating according to claim 2, characterized in that: The atomic percentage of metals in the high entropy alloy is (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%)V.

4. The metal nitride-based composite coating according to claim 1, characterized in that: The thickness of the metal nitride-based composite coating is 1300nm-2000nm.

5. The method for preparing the metal nitride-based composite coating according to claim 1, characterized in that: A Mo transition layer and a MoN-based composite coating of Cr-Al-Ti-Nb-V, MoS2 and Ag were deposited on the surface of the substrate by high-power pulsed magnetron sputtering technology.

6. The preparation method according to claim 5, characterized in that: The method for depositing the Mo transition layer includes: using high-power pulsed magnetron sputtering technology, using Mo as a target material, using an inert gas as a working gas, applying a high-power pulse power supply to the Mo target, and applying a bias voltage at the same time, wherein the inert gas flow rate is 60sccm, the substrate bias voltage is -200 to -300V, the frequency is 80KHz, the pulse width is 6μs, the peak current is 260A, the average output power is 5KW, the frequency is 100Hz, the pulse width is 500μs, and the deposition time is 10 to 15min.

7. The preparation method according to claim 5, characterized in that: The method for depositing MoN-based composite coating comprises: using high-power pulsed magnetron sputtering technology, using Mo, high-entropy alloy compound MoS2 and Ag as target materials, using inert gas as working gas, and inputting nitrogen at the same time, for Mo target, (0.17at%-0.41at%)Cr-(0.08at%-0.21at%)Al-(0.13at%-0.21at%)Ti-(0.08at%-0.13at%)Nb-(0.17at%-0.41at%) %)V composite MoS2 and Ag targets are applied with high-power pulse power and pulse bias at the same time, wherein the peak current of Mo target is 260A, the average output power is 5KW, the frequency is 100Hz, the pulse width is 500μs, the inert gas flow rate is 60sccm, the N2 flow rate is 10sccm~20sccm, the bias voltage is -150V, the frequency is 40KHz, the pulse width is 12μs, the peak current of high entropy alloy composite MoS2 target and Ag target is 40A~80A, and the deposition time is 180min.

Citation Information

Cited By

  • Strong-bonding wide-temperature-range wear-resistant composite coating as well as preparation method and application thereof

    CN120776242A